Air-pollution-satellite-based CO2 emission inversion: system evaluation, sensitivity analysis, and future research direction - H. Li; H. Li; J. Qiu; J. Qiu; B. Zheng; B. Zheng (Atmospheric Chemistry and Physics)
Simultaneous monitoring of greenhouse gases and air pollutant emissions is crucial for combating global warming and air pollution. We previously established an air-pollution-satellite-based carbon dioxide (CO2) emission inversion system, successfully capturing CO2 and nitrogen oxide (NOx) emission fluctuations amid socioeconomic changes. However, the system's robustness and weaknesses have not yet been fully evaluated. Here, we conduct a comprehensive sensitivity analysis with 31 tests on various factors including prior emissions, model resolution, satellite constraint, and inversion system configuration to assess the vulnerability of emission estimates across temporal, sectoral, and spatial dimensions. The relative change (RC) between these tests and base inversion reflects the different configurations' impact on inferred emissions, with 1 standard deviation (1σ) of RC indicating consistency. Although estimates show increased sensitivity to tested factors at finer scales, the system demonstrates notable robustness, especially for annual national total NOx and CO2 emissions across most tests (RC < 4.0 %). Spatiotemporally diverse changes in parameters tend to yield inconsistent impacts (1σ ≥ 4 %) on estimates and vice versa (1σ < 4 %). The model resolution, satellite constraint, and NOx emission factors emerge as the major influential factors, underscoring their priority for further optimization. Taking daily national total CO2 emissions as an example, the <mover accent="true"><mtext>RC</mtext>‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="18pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="b2cd05ee42047bdc6dc921bdbf5ea2f5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1949-2025-ie00001.svg" width="18pt" height="13pt" src="acp-25-1949-2025-ie00001.png"/></svg:svg> ± 1σ they incur can reach −1.2 ± 6.0 %, 1.3 ± 3.9 %, and 10.7 ± 0.7 %, respectively. This study reveals the robustness and areas for improvement in our air-pollution-satellite-based CO2 emission inversion system, offering opportunities to enhance the reliability of CO2 emission monitoring in the future.